Multi-response optimization of dry sliding wear parameters of AA6026 using hybrid gray relational analysis coupled with response surface method. (June 2019) - Gajalakshmi, K; Senthilkumar, N; Prabu, B
Experimental study on dry sliding wear properties of aluminum alloy 6026 were performed utilizing pin-on-disk wear testing machine, considering the wear parameters like the applied load on the pin and the rotational and track diameter of disk. Wear of the pin, coefficient of friction and frictional force were observed during the test procedure for analysis. The experimental trials were designed by L16 Orthogonal Array based on Taguchi's design of experiments and a hybrid approach of gray relational analysis combined with response surface methodology was applied for optimizing the output responses. The optimum conditions obtained for lower wear, coefficient of friction and frictional force were 35.21 N load, 376 r/min speed of disk and 111.53 mm disk track diameter, respectively. Scanning electron microscopy image of specimens taken after testing shows that abrasive wear mechanism is the predominant mechanism of wear. Experiment of confirmation with optimum conditions shows that the result was nearer to the predicted results.